Coping strategies employed by urban adolescents from divorced families to pursue secondary education in Tanzania - Rashidi, Zainabu (Papers in Education and Development, 2024)
This study explored the coping strategies used by urban secondary school adolescents from divorced families in Tanzania to pursue their education. Using a phenomenological design, 34 participants were purposively selected from Ilala Municipality in Dar es Salaam. Data were collected through semi-structured interviews and focus group discussions and analysed thematically. The results revealed that adolescents adopt diverse coping mechanisms, including personal resilience, self-control, social withdrawal, assisting custodial parents in small businesses, engaging in spiritual activities, and maintaining academic focus. Notably, parental conflicts significantly shape these strategies, highlighting the need for effective communication between adolescents, parents, and extended family members. The study concludes that supporting adolescents from divorced families requires a holistic, collaborative approach involving families, schools, and communities. It recommends the establishment of structured communication platforms in schools and the development of community-based support programmes tailored to adolescents' needs to promote their well-being and academic achievement.